Legal Certainty of Intellectual Property That Becomes an Object of Debt Collateral in Bank Financial Institutions According to Government Regulation Number 24 of 2022 - Arif Budi Kusuma; Suherman Suherman (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The purpose of this study is to understand the form of intellectual property regulation that is the object of debt collateral in bank financial institutions and the form of execution of intellectual property that is the object of debt collateral in bank financial institutions in the event of default according to Government Regulation Number 24 of 2022. This study uses a normative legal research method with a statutory regulatory approach and a conceptual approach. The legal materials used include primary legal materials in the form of legislation covering intellectual property and collateral, secondary legal materials in the form of interviews with Rikson Sitorus as Chair of the Legal Analyst Working Group for Copyright and Industrial Design, DJKI, Ministry of Law and Human Rights and Muhammad Fauzy as Coordinator of Intellectual Property Facilitation II, Ministry of Tourism and Creative Economy/Baparekraf, scientific papers and related documents. The validity of legal materials is carried out by harmonizing legal materials in order to find the suitability of legal materials with the issues being answered. Based on the research results, it was found that: (1) Intellectual Property as an object that has a movable and intangible nature, the same as other property rights, can be transferred and assigned to other parties, such as being used as a credit guarantee object by the owner of the intellectual property. PP 24 of 2022 opens up opportunities for all types of IP to be used as bank collateral. (2) Execution of IP as Collateral can be carried out by; if the collateral is bound by fiduciary, it can be executed following the provisions contained in the Collateral Law, if using a contract in creative economic activities, the settlement process is carried out based on the provisions of the existing contract, if using the right to collect in creative economic activities, the right to collect can be executed by demanding payment through a legal process in accordance with the existing agreement.